Anti-Inflammatory and Antioxidant Activities of Thai Traditional Remedy Called “Ya-Ha-Rak” - Juckmeta, Thana; Itharat, Arunporn (Journal of Health Research, 2017)
Benjalokawichien (BLW) or Ya-Ha-Rak remedy (HR) is the drug list in herbal medicinal products A.D 2011 of Thailand and used as antipyretic drug and treat rash in Thai Traditional Medicine. Its plant ingredients consists with five plant roots such as Ficus racemosa Linn., Capparis micracantha DC., Clerodendrum petasites S. Moore., Harrisonia perforata Merr., Tiliacora triandra Diels. This study are investigation anti-inflammatory and antioxidant, activities of the extract of HR and its plant components by inhibitory activity on the release of inhibitory activities against lipopolysaccharide (LPS) induced nitric oxide (NO) production in RAW 264.7 cell lines and DPPH scavenging assays respectively. HR extract possessed the highest NO inhibitory activity with an IC50 value of 40.4µg/ml. The ethanolic extract of Ficus racemosa exhibited the highest antioxidant activity (IC50= 4.9 µg/ml) and HR extract also show antioxidant activity (EC50=40.9µg/ml). This study can support the use of HR in Thai Traditional Medicine for treatment inflammatory diseases.